2011
DOI: 10.1021/jf202057x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Metabolite Profile and Technological Properties of Bovine Milk from Two Dairy Breeds Elucidated by NMR-Based Metabolomics

Abstract: The aim of the present study was to investigate the relationship between the metabolite profile of milk and important technological properties by using nuclear magnetic resonance (NMR)-based metabolomics. The metabolomics approach was introduced for the metabolic profiling of a set of milk samples from two dairy breeds representing a wide span in coagulation properties. The milk metabolite profiles obtained by proton and carbon NMR spectroscopy could be correlated to breed and, more interestingly, also with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 30 publications
3
93
2
1
Order By: Relevance
“…It was shown recently that 16% of all milk from Swedish Red (SR) cows was classified as noncoagulating (NC; Poulsen et al, 2013). Furthermore, we have previously shown that the low-molecular-weight metabolites in milk are correlated with rennet-induced coagulation properties (Sundekilde et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…It was shown recently that 16% of all milk from Swedish Red (SR) cows was classified as noncoagulating (NC; Poulsen et al, 2013). Furthermore, we have previously shown that the low-molecular-weight metabolites in milk are correlated with rennet-induced coagulation properties (Sundekilde et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…In milk processing, it has been shown that cows with higher levels of citrate content in milk have better flavor profiles in fermentation and cheese aging and heat stability; however, high levels of citrate are also associated with poor coagulation properties (Sundekilde et al, 2011). This explains the common practice in commercial cheese making of adding calcium chloride in cheese making before the enzymatic coagulation step so coagulation takes place normally, but aging cheeses with high citrate levels develop better flavors (Dudley and Steele, 2005;Brickley et al, 2009).…”
Section: Association Between Target Gene Genotypes and Citrate Contentmentioning
confidence: 99%
“…Citrate content, choline, and carnitine are associated with milk coagulation properties (Sundekilde et al, 2011). Citrate is a normal constituent of milk and forms one of the main buffer systems that regulates the equilibrium between Ca 2+ and H + ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the metabolic profile can be accomplished using a variety of analytical platforms, including gas chromatography-mass spectrometry, liquid chromatography-mass spectrometry, and nuclear magnetic resonance (NMR) spectroscopy. Compared with the two chromatographic platforms, NMR-based analysis requires simple and easy sample preparation, which is beneficial for minimizing changes in the chemical composition and reducing the loss of minor components (8,9); simultaneously monitors various organic chemical species (10,11); and shows the potential for efficient high-throughput screening (12). Therefore, the application of an NMR-based platform in metabolomics has been widely reported for studies with a variety of microorganisms, including studies of metabolic flux changes in Escherichia coli during heat (13) and superoxide (14) stresses and the role of genes in Saccharomyces cerevisiae (15,16).…”
mentioning
confidence: 99%